Bridging the digital divide: how does rural digitalization promote rural common prosperity? - Zhou, Xiaoli; Wang, Yunxuan; Han, Mingyang (Frontiers in Earth Science, 2025)
Achieving common prosperity is a long-term and challenging historical process globally, with particularly arduous tasks facing rural areas. Digital rural development provides material guarantees for realizing common prosperity in rural areas. This paper calculates the digital rural development and rural common prosperity levels across provinces from 2011 to 2021, creates Kernel density plots, and preliminarily demonstrates the dynamic evolutionary trends of China’s digital rural development and common prosperity. Furthermore, panel data analysis is employed to investigate the impact effects, mechanisms, and spatial spillovers of digital rural development on rural common prosperity. The research shows that the development of digital rural areas exhibits significant heterogeneity across different domains, periods, and regions. Additionally, government central transfer payment policies can effectively enhance rural common prosperity levels. However, excessively strict environmental regulatory policies (pollution discharge fees) may inhibit the effectiveness of digital rural development on rural common prosperity. Finally, spatial modeling reveals that digital rural development has significant spillover effects on improving rural common prosperity, generating positive “dividend” effects for adjacent regions, though these dividends gradually diminish with increasing distance.